Ternary Metal Chalcogenide Heterostructure (AgInS(2)–TiO(2)) Nanocomposites for Visible Light Photocatalytic Applications - Ganguly, Priyanka (ACS Omega, 2019)
[Image: see text] Hybrid nanoarchitectures of AgInS(2) and TiO(2) photocatalysts were prepared by using a modified sol–gel method. The experimental results reveal that these nanocomposites display enhanced visible light absorption and effective charge carrier separation compared to their pristine parent samples (AgInS(2) or TiO(2)). 0.5 wt % AgInS(2) loading was found to be the optimum concentration for photocatalytic applications. More than 95% of doxycycline degradation was achieved within 180 min of solar light illumination. Similarly, the dopant concentrations at lower values (<2 wt %) exhibited 300 times higher H(2) generation rate under visible light irradiation compared to AgInS(2) and TiO(2). The microbial strains (Escherichia coli and Staphylococcus aureus) exhibited a 99.999% reduction within half an hour of simulated solar light illumination. The computational investigation was employed to understand the structural, electronic, and the dielectric properties of AgInS(2) and TiO(2) composites. The improved photocatalytic results are explained as a result of the decreased rate of exciton recombination. The current investigation opens up new insights into the use of novel ternary heterostructure nanocomposites for improved visible light activity.